2010
DOI: 10.3109/13682822.2010.484845
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for naming difficulties in bilingual aphasia: which language benefits?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractBackground: The majority of the world's population is bilingual. Yet, therapy studies involving bilingual people with aphasia are rare and have produced conflicting results. One recent study suggested that therapy can assist word retrieval in bilingual aphasia, with effects generalising to related words in the untreated language. However, this cross-linguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 24 publications
4
42
0
2
Order By: Relevance
“…A lack of generalisation across languages has been reported in a large number of other studies (Abutalebi et al, 2009;Ansaldo, Saidi, & Ruiz, 2010;Byng, Coltheart, Masterson, Prior, & Riddoch, 1984;Bychowsky, 1919;Croft et al, 2011;Galvez & Hinckley, 2003;Gil & Goral, 2004;Goral et al, 2010;Halpern, 1949;Hinckley et al, 2005;Laganaro & Overton-Venet, 2001;Kiran & Roberts, 2010;Kohnert, 2004;Meinzer et al, 2007;Miertsch et al, 2009 (for L1);Miller, 1993;Minkowski, 1927Minkowski, , 1949Minkowski, , 1964Sasanuma & Park, 1995;Watamori & Sasanuma, 1976. Abutalebi et al (2009) reported improved naming in L2 (Italian) but no improvement of naming in L1 (Spanish) following intervention in L2.…”
Section: Evidence Of Lack Of Therapy Transfer Across Languagesmentioning
confidence: 89%
See 3 more Smart Citations
“…A lack of generalisation across languages has been reported in a large number of other studies (Abutalebi et al, 2009;Ansaldo, Saidi, & Ruiz, 2010;Byng, Coltheart, Masterson, Prior, & Riddoch, 1984;Bychowsky, 1919;Croft et al, 2011;Galvez & Hinckley, 2003;Gil & Goral, 2004;Goral et al, 2010;Halpern, 1949;Hinckley et al, 2005;Laganaro & Overton-Venet, 2001;Kiran & Roberts, 2010;Kohnert, 2004;Meinzer et al, 2007;Miertsch et al, 2009 (for L1);Miller, 1993;Minkowski, 1927Minkowski, , 1949Minkowski, , 1964Sasanuma & Park, 1995;Watamori & Sasanuma, 1976. Abutalebi et al (2009) reported improved naming in L2 (Italian) but no improvement of naming in L1 (Spanish) following intervention in L2.…”
Section: Evidence Of Lack Of Therapy Transfer Across Languagesmentioning
confidence: 89%
“…Spoken expression and reading was regained in Russian only, after the onset of treatment. Croft et al (2011) found no cross-language therapy benefits following phonological naming intervention from L1 to L2 or from L2 to L1 for a group of mixed proficiency bilinguals with aphasia who spoke Bengali (L1) and English (L2). Semantic naming intervention in L2 benefited L1 for one of the five participants, and in L1 benefited L2 for two participants.…”
Section: Evidence Of Lack Of Therapy Transfer Across Languagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Concerning cross-language generalisation patterns induced by semantic or phonological therapies, semantic therapy has been reported to induce CLG in studies with bilingual aphasic patients (Croft, Marshall, Pring, & Hardwick, 2011;Edmonds & Kiran, 2006;Kiran et al, 2013;Kohnert, 2004;Miertsch, Meisela, & Isel, 2009). In contrast, although Hinckley (2003) and Marangolo et al (Marangolo, Rizzi, Peran, Piras, & Sabatini, 2009) showed some level of CLG with mixed semantic-phonological therapy or using phonological therapy in L2, CLG was not found after phonological therapy in Meinzer et al (Meinzer, Obleser, Flaisch, Eulitz, & Rockstroh, 2007), or transfer was limited to phonologically similar words (cognates) (Kohnert, 2004;Pillon & de Partz, 2005).…”
Section: Introductionmentioning
confidence: 99%